Ruang Lingkup Teknologi Pendidikan Agama Islam di Era Indrustri 4.0 - Ahmad Budiyono (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2019)
Technology is a whole system for managing results to create added value. The use of technology is very useful in the world of education, including in Islamic education. Don't misinterpret that educational technology is not only related to technical equipment and media used in education, such as: overhead, projectors, televisions, slide projectors, audio tapes, video recordings and so on. Educational technology can be defined as the development, application and evaluation of systems, techniques and tools for the purpose of improving the teaching and learning process for humans. The use of technology or media in the learning process must be adjusted to the lessons delivered so that the results obtained are optimal. In addition, it is also adjusted to the ability of students. Based on developments in the fields of technology, education and other relevant scientific disciplines as a basis for learning technology, there are a number of areas cultivated in Islamic education learning technology which include areas a) design areas, b). Development area, c). area of ??utilization, d). management area.